2013
DOI: 10.1007/s11046-013-9718-0
|View full text |Cite
|
Sign up to set email alerts
|

PCR as a Screening Test for Invasive Aspergillosis in Haematological Patients: A Pilot Study

Abstract: Invasive aspergillosis is a leading cause of morbidity and mortality in immunocompromised patients, particularly in individuals with haematological malignancy and in haematopoietic stem cell transplant recipients. Nowadays, the galactomannan (GM) assay has been widely used as an indication of invasive aspergillosis, even though the test is known to generate false-positive results. The aim of this study was to compare the performance of GM and real-time PCR (qPCR) to detected Aspergillus in blood samples obtain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…This technique relies on amplification of the inter-transcribed (ITS) ribosomal region, or the 28S or 18S rRNA genes[ 18 , 19 , 28 ]. However, due to inefficient DNA extraction procedures, the requirement for large samples volumes[ 29 ], and non-standardized approaches, it has been suggested that qPCR and PCR be used as a confirmatory test rather than an initial diagnostic test[ 30 , 31 ] or in combination with other approved diagnostic tests[ 18 , 19 ]. Due to the problems associated with all of the current approaches and the need to treat invasive fungal infections in a timely manner, new diagnostic methods for IA are needed to improve clinical outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…This technique relies on amplification of the inter-transcribed (ITS) ribosomal region, or the 28S or 18S rRNA genes[ 18 , 19 , 28 ]. However, due to inefficient DNA extraction procedures, the requirement for large samples volumes[ 29 ], and non-standardized approaches, it has been suggested that qPCR and PCR be used as a confirmatory test rather than an initial diagnostic test[ 30 , 31 ] or in combination with other approved diagnostic tests[ 18 , 19 ]. Due to the problems associated with all of the current approaches and the need to treat invasive fungal infections in a timely manner, new diagnostic methods for IA are needed to improve clinical outcomes.…”
Section: Introductionmentioning
confidence: 99%